1999
DOI: 10.1177/109019819902600105
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Abstinence and Condom Use: Are We Sure We Are Really Teaching What is Safe?

Abstract: This article reviews existing research on condom and abstinence method- and user-failure rates, and the use of this research in determining sexuality education curricula. Latex condoms effectively prevent pregnancies and most sexually transmitted diseases or infections (STIs), with method-failure rates between 0.5% and 7%, but with user-failure rates between 12% and 70%. Total abstinence presumably has a method-failure rate of zero, but research on periodic abstinence indicates user-failure rates between 26% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…15 There is some consensus that sexuality education and interventions with some abstinence-based or "abstinence-plus" curriculum components are most effective when targeted at younger adolescents before they become sexually active. 1,41 Some recent studies demonstrated the importance of youth, parent, physician, and education partnerships for the prevention of health risk behaviors such as early initiation of sexual intercourse. 13,42 One study illustrated that an abstinence-only curriculum had no significant impact on the initiation of sex, the frequency of sex among those students who had ever had sex, or the number of sexual partners among those who had ever had sex.…”
Section: Methods Of Contraceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 There is some consensus that sexuality education and interventions with some abstinence-based or "abstinence-plus" curriculum components are most effective when targeted at younger adolescents before they become sexually active. 1,41 Some recent studies demonstrated the importance of youth, parent, physician, and education partnerships for the prevention of health risk behaviors such as early initiation of sexual intercourse. 13,42 One study illustrated that an abstinence-only curriculum had no significant impact on the initiation of sex, the frequency of sex among those students who had ever had sex, or the number of sexual partners among those who had ever had sex.…”
Section: Methods Of Contraceptionmentioning
confidence: 99%
“…Two other studies produced similar results. 1 The AAP supports a comprehensive approach to sexuality education for adolescents. Abstinence should play a part in any comprehensive discussion of sexuality, and resources should be made available for adolescents who feel pressured, but prefer not, to engage in sexual activity.…”
Section: Methods Of Contraceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, adolescents are freely left to watch unmoderated TV films, which might be contributing on teenagers' behavior change towards earlier sexual engagement [11,12]. To date, a controversial question still lingers on whether we are teaching what is safe for our Zambian adolescents or not [13]? The bottom line is that casual and unprotected sexual activities among most juveniles begin much earlier than their parents may expect [14].…”
Section: *Correspondencementioning
confidence: 99%
“…Method failure occurred when a contraceptive method is ineffective due to a defect on the product itself while user failure is due to incorrect or inconsistent use of the product. 4 There has been controversy on how effective male latex condom is in preventing conception and transmission of STIs. Studies on the effectiveness of male latex condom in preventing conception and transmission of STIs gave a wide range of condoms effectiveness (prevention of conception and transmission of STIs) and failures (condoms breakage and slipping).…”
Section: Introductionmentioning
confidence: 99%